Manifest heritages of family and nation: embodying "all the ancestors" in Guyanese Komfa - Peretz, Jeremy Jacob (Journal of Africana religions, 2020)
This article offers comparative ethnographic exploration of Komfa ritual engaged to "entertain the ancestors" that is central to the way of life of Spiritualists in Guyana. Practiced primarily by Guyanese of African descent and considered an Africa-derived tradition, Komfa worldview nonetheless draws on cultural inheritances of various Guyanese backgrounds. Embracing Komfa worlds serves as historical and genealogical inquiry into often indistinct, polysemous pasts wherein spirit guides lead devotees through emancipatory journeys of familial and personal (re)discovery. Komfa can best be understood through comparative analyses foregrounding "adjacent" Black Atlantic religious idioms. Frameworks developed in interrogating practices at the "margins" of Candomblé, Lukumí, and Vodou situate Komfa and the spectrum that African-inspired religions encompass. In particular, existing ethnographic literature on Espiritismo as practiced in Cuba and elsewhere furnishes critical perspectives through which to understand Komfa that are more adequate than the bodies of scholarship consulted by researchers studying Komfa thus far.